Rural Young Adults' Lay Theories of Intimate Partner Violence: A Qualitative Examination. Issue 3 (24th October 2016) - Edwards, Katie M.; Banyard, Victoria L.; Moschella, Elizabeth A.; Seavey, Katherine M.
Abstract: This study qualitatively examined rural emerging adults' ways of thinking (i.e., lay theories) about the causes of intimate partner violence (IPV) and ideas on how to prevent IPV most effectively. Participants were 74 individuals (majority Caucasian, heterosexual, low income) between the ages of 18 and 24 who resided in one of 16 rural communities. Participants' perceptions of the causes of IPV included (a) individual‐level pathology, stress, and lack of education; (b) intergenerational transmission of violence and early‐life factors; (c) relationship stressors and challenges; and (d) community factors. Furthermore, participants felt that IPV could most effectively be prevented through (a) education and awareness; (b) victim‐focused efforts (e.g., teaching self‐esteem); and (c) job creation. Overall, participants identified a number of established risk factors for IPV perpetration across the social ecological model, although a number were never or rarely mentioned (e.g., peer group norms, positive bystander action, and collective efficacy). Future research should examine if and how perceptions of the causes of IPV impact IPV prevention engagement and impact. Further, prevention initiatives that take into account understandings of lay theories about IPV may be more impactful in reducing IPV than prevention initiatives that do not.